A new species of Leptomastax Pirazzoli in Israel (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2024)
Leptomastax Pirazzoli includes 25 species mainly distributed in the Mediterranean region. Leptomastax minutissima sp. n. is described, based on a male collected in northern Israel. This is the smallest member of this genus known so far, with the body length merely 1.13 mm, and it belongs in a group of eyeless species with a strongly reduced pattern of macrosetae. Identification key to Leptomastax of Israel is given.